The Principles of Model Law Regarding the Implementation of Estate Execution in Transnational Bankruptcy Cases - Putriana, Fafta Aini; Fairuzzaman, Fahmi; Hidayat, Akbar (PDIH Untag Semarang, 2024)
This research is important to find out what system should be used to create legal certainty regarding the execution of transnational bankruptcy cases. The purposes to be achieved are, first, to know the system that works within the principles of the Model Law developed by the United Nations in handling transnational bankruptcy execution cases. Second, knowing how national law creates execution rules if the foreign debtor's bankruptcy assets are in Indonesia's jurisdictionUsing juridical-normative research methods, the author attempts to analyze transnational bankruptcy based on international and national regulations. International rules are regulated in UNCITRAL: Model Law created by the UN and is a legal reference for countries that have transnational bankruptcy legal instruments with reference to this Model Law. Meanwhile, the national regulations are in Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations, which became known as UUK-PKPU. Model Law regulations provide legal certainty regarding transnational bankruptcy. different from national legal rules which are limited by jurisdiction. The substance of the Model Law provides an opportunity for foreign parties to participate in solving problems. The conclusion of this research is that the adoption of the Model Law by several countries will provide greater convenience and legal certainty in the field of bankruptcy law, especially transnational bankruptcy.